Kesesuaian Lahan Budidaya Lobster (Panulirus spp.) Sistem Keramba Jaring Apung Menggunakan Pendekatan Sistem Informasi Geografis - Arif Prasetya; La Ode Abdul Fajar Hasidu; Arif Prasetya (Jurnal Airaha, 2021)
This research is to identify and mapping some parameters of oceanography that suitable for lobster aquaculture activities with floating net cage systems and produce recommendations of a spatial map of the feasibility of floating net cage lobster farming. This research was conducted in July 2021 located in the coastal area of Kolaka. The oceanography data was collected from 58 stations and analyzed by Arc GIS 10 software. To produce a map of land suitability, the data was analyzed by interpolation and spatial clasification method before being overlaid in every oceanography parameter to be scored based on a suitability matrix. Regarding the land suitability map, it exhibited that the width of the Kolaka coastal area which is suitable for lobster farming with the floating net cage system was 7.973 Ha. Meanwhile, 9.519 Ha coastal area was not suitable.